2010
DOI: 10.1242/dev.043604
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Hey is a target of Notch in asymmetric divisions during embryonic and larval neurogenesis

Abstract: bHLH-O proteins are a subfamily of the basic-helix-loop-helix transcription factors characterized by an ‘Orange’ protein-protein interaction domain. Typical members are the Hairy/E(spl), or Hes, proteins, well studied in their ability, among others, to suppress neuronal differentiation in both invertebrates and vertebrates. Hes proteins are often effectors of Notch signalling. In vertebrates, another bHLH-O protein group, the Hey proteins, have also been shown to be Notch targets and to interact with Hes. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 62 publications
4
67
1
Order By: Relevance
“…Despite the near extinction of E(spl)m and m8 expression, no obvious effect was seen in Notch pathway mutant type I lineages in the larva: they consisted of one Dpn-positive NB, 2-5 GMCs and several neurons, as noted before (Almeida and Bray, 2005;Monastirioti et al, 2010;San-Juán and Baonza, 2011). Instead, type II clones were recovered less efficiently and showed reduced proliferation (supplementary material Fig.…”
Section: Research Articlementioning
confidence: 94%
See 2 more Smart Citations
“…Despite the near extinction of E(spl)m and m8 expression, no obvious effect was seen in Notch pathway mutant type I lineages in the larva: they consisted of one Dpn-positive NB, 2-5 GMCs and several neurons, as noted before (Almeida and Bray, 2005;Monastirioti et al, 2010;San-Juán and Baonza, 2011). Instead, type II clones were recovered less efficiently and showed reduced proliferation (supplementary material Fig.…”
Section: Research Articlementioning
confidence: 94%
“…Primary antibodies were rabbitanti--gal (Cappel); rat-anti-Elav 7E8A10 (DSHB); rabbit-anti-GFP (Minotech); mouse-anti-GFP (Molecular Probes); guinea-pig-anti-Hey (Monastirioti et al, 2010); rat-anti-Dpn (Boone and Doe, 2008); rabbitanti-Ase (a gift from A. Jarman, University of Edinburgh, UK); mouseanti-Pros MR1A (DSHB); and mouse-anti-CycE (a gift from H. Richardson, Peter MacCallum Cancer Centre, Melbourne, Australia).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry was performed as previously described (Baumgardt et al, 2009). Primary antibodies were: guinea pig anti-Hey [1:500; provided by C. Deldiakis (Monastirioti et al, 2010)]; guinea pig anti-Deadpan (1:1000; provided by J. B. Skeath); rabbit anti-phospho-histone H3 Ser10 (pH3) (1:250; Upstate/Millipore, Billerica, MA, USA); rabbit anti--gal (1:5000; ICN-Cappel, Aurora, OH, USA); rabbit anti-cleaved Caspase 3 (1:100; Cell Signaling Technology, Danvers, MA, USA); chicken anti--gal (1:1000; Abcam, Cambridge, UK); rabbit anti-GFP (1:500; Molecular Probes, Eugene, OR, USA); guinea pig antiCol (1:1000), guinea pig anti-Dimm (1:1000), chicken anti-proNplp1 (1:1000) and rabbit anti-proFMRFa (1:1000) (Baumgardt et al, 2007); rat anti-Grh (1:1000) (Karlsson et al, 2010); rabbit anti-Nab [1:1000; provided by F. Díaz-Benjumea (Terriente Felix et al, 2007)]; rabbit anti-Cas [1:250; provided by W. Odenwald (Kambadur et al, 1998)]; rat mAb anti-GsbN [1:10; provided by R. Holmgren (Buenzow and Holmgren, 1995)]; mouse mAb anti-Dac dac2-3 (1:25), mAb anti-Antp (1:10), mAb anti-Pros MR1A (1:10), mAb anti-Eya 10H6 (1:250) and mAb anti-NICD (1:10) (Developmental Studies Hybridoma Bank, Iowa City, IA, USA); rabbit anti-Inscutable [1:1000; provided by F. Yu and W. Hongyan, Temasek Lifesciences Laboratory (TLL), National University of Singapore, Singapore)]; rat anti-Miranda (1:100; provided by F. Matsuzaki, Center for Developmental Biology, RIKEN, Kobe, Japan); and guinea pig anti-Numb (1:1000; provided by J.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In addition, we assayed Notch pathway activation in an indirect manner by analyzing the expression of well-known Notch target genes: members of the HES (Hairy, Enhancer of Split) family of bHLH transcription factors (reviewed by Bray, 2006), as well as the HES-related Notch target Hey (Monastirioti et al, 2010). Hey has recently been found to be expressed in many 'A' cells (Notch-activated sibling neurons and/or glia) and to depend upon Notch signaling for its expression (Monastirioti et al, 2010). In line with this, we found that postmitotic cells in the early part of the lineage express Hey (Fig.…”
Section: The Nb5-6t Lineage Progresses Via Typical Asymmetric Cell DImentioning
confidence: 99%